How and why people use camera phones - Sellen, Abigail; Fleck, Rowanne; Kindberg, Tim; Spasojevic, Mirjana (Microsoft, 2004)
In this paper we describe an in-depth study into how people (adults and young people) use their camera phones. Using a combined method of interviews and grounded discussions around a sample of actual photos, we look at people’s intentions at the time of capture, subsequent patterns of use, and desires for future technology. The result is a 6-part taxonomy which provides a framework for describing the way images are used both for sharing and personal use, and for affective (or emotional) reasons and functional use. On the basis of this framework, we discuss the value of camera phones and point to ways in which future design may encourage its emerging value.